Serum Levels of Interleukin-10 and D-Dimer as Biomarkers of Coronavirus Disease (Journal of Pharmaceutical Negative Results, 2022)
Background: Coronavirus 2019 is one of the most remembered pandemics, and it is regarded as one of the most significant occurrences of the twenty-first century. Clinical signs and symptoms, as well as reverse transcription-polymerase chain reaction (RT-PCR) test, are used to diagnose COVID19. Several biomarker molecules are being researched for their potential utility in evaluating the severity and prognosis of severe acute respiratory syndrome corona virus-2 (SARS-CoV-2). This study was designed to assess the level of IL-10 and D-Dimer in patients who were suffering from COVID-19.Materials and Methods: This prospective study included 168 participants who were attending Imam Hussein Hospital in Karbala. They were divided into two groups (I & II) based on the result of RT-PCR test; IL-10 and D-Dimer were analyzed for studied groups. Results: The median age of 41.6 years, 86 males and 82 females. A noteworthy increase was observed in the level of IL-10 (9.803 ± 0.44) and D-Dimer (1511.534±192.56) in the positive PCR group as compare with negative PCR group. Conclusion: The levels of IL-10 and D-Dimer can be utilized to estimate the severity and prognosis of COVID-19 patients, according to our findings. D-dimer levels, among these biomarkers, correspond more closely with severity and can be used as a solid prognostic indicator.